BORROWING WORDS: ORAL AND WRITTEN BORROWINGS - Rahmonova Dilnoza Toshmirzayevna (Galaxy International Interdisciplinary Research Journal, 2023)
The lexical layer of the Uzbek language the development of the Uzbek lexical layer can also be studied based on certain stages of the society, taking into account significant changes in the society. Uzbek, as Turkish language, has been in Central Asia for centuries, along with Persian development can also be studied through a series of stages, taking into account significant changes in society. Uzbek, as Turkish language, has been in Central Asia for centuries, along with Persian.